Galactomannan detection in bronchoalveolar lavage fluids: A diagnostic approach for fungus ball in patients with pulmonary tuberculosis?. Issue 7 (24th May 2020) - Gheisari, Maryam; Basharzad, Niloofar; Yazdani Charati, Jamshid; Mirenayat, Maryam Sadat; Pourabdollah, Mihan; Ansari, Saham; Mortezaee, Vida; Abastabar, Mahdi; Jafarzadeh, Jalal; Haghani, Iman; Hedayati, Mohammad T.
Abstract: Background: Several previous studies have shown cavitary lung lesions in old pulmonary tuberculosis (PTB) increase the risk of fungus ball. Detection of galactomannan (GM) in bronchoalveolar lavage (BAL) is also proposed as a diagnostic approach for the fungus ball. Objectives: We evaluated the diagnosis of fungus balls and GM levels in BAL samples in PTB patients. Methods: A total of 110 PTB patients were evaluated for fungus ball during 2017‐2019. The patients were evaluated for radiological, histopathological results and mycological findings of BAL including GM detection and culture. The sensitivity, specificity and positive and negative predictive value for GM test were calculated. The optimal cut‐off for BAL GM testing was determined by receiver operating characteristic (ROC). Results: Of 110 PTB patients, nine (8.18%) showed fungus ball, all with old PTB. The molecularly confirmed Aspergillus species were A. flavus, A. fumigatus and A. ochraceus . The sensitivity and specificity of BAL GM ≥ 0.5 in old PTB patients with fungus ball were 100%, 41.5%, respectively. The statistical analysis of the mean ± SEM of BAL GM levels was demonstrated a higher levels of GM in patients with fungus ball/aspergilloma compared to old PTB patients without fungus ball/aspergilloma. The optimal cut‐off value for BAL GM was determined as 0.50 by ROC curve analysis. Conclusion: According to our results, we can recommend the detection of GM in BAL samples as a diagnostic approach for fungus ball in PTB patients.